Hsa_circ_0020095 Promotes Oncogenesis and Cisplatin Resistance in Colon Cancer by Sponging miR-487a-3p and Modulating SOX9 - Sun, Yanlai; Cao, Zhen; Shan, Junqi; Gao, Yang; Liu, Xin; Ma, Dejian; Li, Zengjun (Frontiers in Cell and Developmental Biology, 2021)
Objectives: Colon cancer (CC) currently ranks as the third most common human cancer worldwide with an increasing incidence and a poor prognosis. Recently, circular RNAs have been reported to regulate the progression of diverse human cancers. However, the role of circRNA hsa_circ_0020095 in CC remains largely unclear. Methods: Expression levels of the related circRNAs, microRNAs and mRNA in CC tissues and cells were determined. The impacts of circ_0020095 or miR-487a-3p on CC cells were examined at the indicated times after transfection. Meanwhile, a luciferase-reporter experiment was employed to validate the interplay between miR-487a-3p and circ_002009695 or SOX9. Moreover, the in vivo tumor growth assay was applied to further evaluate the effects of circ_0020095 knockdown on CC progression. Results: We demonstrated that circ_0020095 was highly expressed in CC tissues and cells. The proliferation, migration, invasion and cisplatin resistance of CC were suppressed by silencing circ_0020095 in vitro and in vivo or by ectopic expression of miR-487a-3p in vitro. Mechanistically, circ_0020095 could directly bind to miR-487a-3p and subsequently act as a miR-487a-3p sponge to modulate the activity by targeting the 3’-UTR of SOX9. Interestingly, overexpression of circ_0020095 dramatically reversed the suppressive effects of miR-487a-3p mimics on CC cells. Conclusions: circ_0020095 functions as an oncogene to accelerate CC cell proliferation, invasion, migration and cisplatin resistance through the miR-487a-3p/SOX9 axis, which could be a promising target for CC treatment.